A mixed-methods study of challenges and benefits of clinical academic careers for nurses, midwives and allied health professionals. Issue 10 (7th October 2019) - Trusson, Diane; Rowley, Emma; Bramley, Louise
Abstract : Objectives: The clinical academic trajectory for doctors and dentists is well-established, with research embedded in their career development. Recent years have also seen a burgeoning interest and push for nurses, midwives and allied health professionals (NMAHPs) to pursue a clinical academic career. However, the National Institute for Health Research (NIHR) 10-year review suggested that there may be problems with progression post Master's degree level for this group, with nurses and midwives receiving less NIHR funding than allied health professionals. This study responds to these concerns, tracking the progression and exploring experiences of NMAHPs in the East Midlands region of England. Design: An online survey and in-depth interviews were used to capture a wide range of experiences. Participants: 67 NMAHPs who were pursuing a clinical academic career were surveyed, supplemented by 16 semi-structured in-depth interviews. Results: Three themes emerged during data analysis: Embarking on a clinical academic career, overcoming barriers and benefits. Conclusions: NMAHPs are motivated to pursue a clinical academic career by a drive to improve services for the benefit of patients and the National Health Service more widely, as well as for personal development and career progression. People working in these roles have opportunities to explore possible solutions to issues that they encounter in their clinical role through academic study. Findings reveal benefits emanating from the individual level through to (inter)national levels, therefore academic study should be encouraged and supported. However, investment is needed to establish more clinical academic roles to enable NMAHPs to continue to use their experience and expertise post-PhD, otherwise the full extent of their value will not be recognised.